A multi-criteria decision-making framework for addressing youth unemployment in developing countries: Pathways to sustainable solutions - Bouraima, Mouhamed Bayane; Qian, Su; Maxime Sangaré-Oumar, Machioud; Qiu, Yanjun; Zonon, Babatounde Ifred Paterne (Journal of Intelligent Decision Making and Information Science, 2025)
Youth unemployment is among Africa’s most urgent challenges, with over 60% of its population under 25, the largest youth demographic globally. This youthful population presents a significant opportunity to drive economic growth, innovation, and development. However, the lack of sufficient employment opportunities risks perpetuating poverty, inequality, and social instability. To address this issue and unlock Africa’s potential, this study evaluates and prioritizes six strategies identified through a comprehensive literature review and expert input. Using the Stepwise Weight Assessment Ratio Analysis (SWARA) method within an interval-valued spherical fuzzy (IVSF) framework, the research facilitates collective decision-making. It highlights three key strategies as the most appropriates: reforming education systems to align skills with labor market demands, fostering growth in sectors such as agriculture, manufacturing, and tourism, and promoting entrepreneurship to empower Africa’s young innovators. The study offers actionable insights for policymakers to effectively combat youth unemployment and maximize the continent’s demographic advantage.